The garden apothecary : transform flowers, weeds and plants into healing remedies - Cole, Becky (Herbalist) (Hardie Grant Books, 2022)
The Garden Apothecary shows us how to harvest and use commonly found plants, weeds and herbs to create our own healing home apothecaries. With tasty recipes, wild skincare, in-depth plant spotlights and a back-to-roots ethos, The Garden Apothecary will encourage the reader to become more connected to the natural world through learning the art of herbalism from plants growing in our gardens. Focusing on 20 herbs and plants, learn how to identify, grow and pick them from your garden or forage them, as well as discovering their medicinal properties. Each plant and herb spotlight includes at least two recipes to create a tincture, oil, infusion, skin balms or other beauty bits. The Garden Apothecary is a safe and mindful approach to the often overwhelming world of foraging and herbalism.